TO THE QUESTION OF CONSTRUCTING THE REGION OF ALLOWABLE VALUES OF VARIABLE PARAMETERS OF A DIGITAL STABILIZER OF A MOVABLE OBJECT - Eugene Aleksandrov; Tetiana Aleksandrova; Iryna Kostianyk; Yaroslav Morgun (Сучасні інформаційні системи, 2020)
Solving the problems of analysis and synthesis of closed digital systems for stabilization of movable objects is associated with significant difficulties. One of the possible ways to solve the problem is the transition from a mathematical model of a continual-discrete closed stabilization system to an approximate mathematical model of a discrete closed system using infinite matrix series containing the own matrix and the control matrix of the continuous part of the system, as well as the quantization period of the discrete part. Using the example of a closed digital stabilization system for a space stage of a solid-propellant carrier rocket flying in an airless space with a marching engine turned on, the problem of constructing stability regions of a closed digital stabilization system in the plane of variable parameters of a digital stabilizer was solved and a comparative analysis of these regions was carried out for various numbers of members of matrix series taken into account and different values of the digital stabilizer quantization period.